2006
DOI: 10.1248/jhs.52.769
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Functional Nitric Oxide Synthase for Neuritogenesis in PC12h Cells

Abstract: We have previously demonstrated that a natural iridoid compound, genipin, induces neurite outgrowth mediated by nitric oxide (NO) production in PC12h cells. However, genipin could not induce neurite outgrowth by PC12 cells, the parental cells of PC12h cells. The difference in neuritogenic response to genipin may be due to a lack of neuronal NO synthase (NOS) protein, most likely neuronal NOS, in PC12 cells. In this study, we have investigated whether neuronal NOS protein innately expressed in PC12h cells plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…It has been reported that 6-OHDA-induced apoptosis is prevented by NO in PC12 cells. 23) Meanwhile, we have previously reported that genipin induces neuritogenesis through an NO-cGMP-PKG pathway in PC12h [5][6][7] and Neuro2a cells. 8) Therefore, genipin might exert the protective effect observed here via NO production, and this possibility should therefore be investigated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that 6-OHDA-induced apoptosis is prevented by NO in PC12 cells. 23) Meanwhile, we have previously reported that genipin induces neuritogenesis through an NO-cGMP-PKG pathway in PC12h [5][6][7] and Neuro2a cells. 8) Therefore, genipin might exert the protective effect observed here via NO production, and this possibility should therefore be investigated.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously reported that genipin markedly induces neurite outgrowth through a nitric oxide (NO)-guanosine 3 ,5 -cyclic monophosphate (cGMP)-cGMP-dependent protein kinase (PKG) pathway followed by extracellular signal-regulated kinase (ERK) activation in rat pheochromocytoma PC12h [5][6][7] and mouse neuroblastoma Neuro2a cells. 8) This signaling pathway was observed in the neurite outgrowth process induced by NGF in PC12h cells.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Aside from the proteins already mentioned, which are specific to the different UPR pathways, there are several proteins that are associated with more than one of the UPR pathways or other cellular pathways that may be associated with ER stress (Table 4). [25,30,33,44,[102][103][104][105][106][107][108][109] Is there a role for terpenoids from medicinal plants in alleviating endoplasmic reticulum stress and metabolic disorders?…”
Section: Thapsigargin Also Classified As a Guaianementioning
confidence: 99%
“…In Neuro2a cells, genipin has shown to have neuroprotective effects against the cytotoxicity reaction induced by serum deprivation and oxidative stress. [30,44,[102][103][104][105][106][107][108] Cannabidiol (CBD) Calnexin CBD up-regulates the expression of calnexin in mouse HSC LX-2 cells. [25] Parthenolide NF-κB Parthenolide modifies the p65 subunit of the nuclear factor by alkylation on the cysteine residues, inhibiting its activity in Jurkat T cells.…”
Section: Dehydrocostuslactonev (Dhe) Genipinmentioning
confidence: 99%
“…We have also reported that one of the target molecules of genipin in vitro is neuronal NO synthase (nNOS), [6][7][8][9] which suggests that nNOS plays a crucial role in neurotrophic activities of genipin. Moreover, we have also described the neuroprotective effects of genipin on cytotoxicity induced by b-amyloid peptide in rat primary hippocampal neurons, 10) and serum deprivation 11) and oxidative stress 12) in Neuro2a cells, and on trauma-and scopolamine-induced impairment of memory in mice.…”
mentioning
confidence: 95%